Názory na čarodějnictví u Nigerijců žijících v České republice - Jeřábková, Petra (Lidé města, 2004)
The Nigerian ethnic community is one of the modem ethnic groups in the Czech Republic. Situated in an emerging mosaic of varied cultures, the Nigerian community brings incentives that in many cases do not relate to the system of European culture. A belief in the power of witchcraft is one such cultural area. The question of the importance of magic and witchcraft in the Czech Republic is a central theme for the article. It was examined by qualitative research of Nigerians living in Prague and other Czech cities. Research has shown that the life of Nigerians living in the Czech Republic is not only intertwined with their initial culture. Ingrained by enculturation, the belief in the effectiveness and formative result of witchcraft practices influences their own actions. Nigerians attribute the ability to use magic and witchcraft also to their European or Czech friends, neighbours and colleagues. Thus, when reflecting the reality in a European or Czech context, Nigerians apply the culturally based and reliable concept of worldview.